Sodium manganate composite positive electrode material and preparation method thereof

By depositing multilayer sodium manganate composite materials on a substrate using magnetron sputtering, a nanocrystalline structure with rich composition is formed, which solves the problems of single composition and insufficient performance of existing sodium manganate cathode materials and achieves a high-efficiency improvement in battery performance.

CN119340366AActive Publication Date: 2025-01-21HENAN SOLID LITHIUM BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411475856.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing sodium manganate cathode materials have a single composition, which fails to leverage the advantages of composite materials and cannot form nanocrystals, thus failing to fully utilize rare earth elements to improve performance.

Method used

A multilayer sodium manganate composite material, including Na1.0Mn0.7Fe0.1Cu0.1Nd0.1O2, Na1.0Mn0.7Fe0.05Cu0.05Nd0.2O2, Na1.0Mn0.7Fe0.1Ti0.1Ce0.1O2, Na1.0Mn0.7Fe0.1Al0.1Gd0.1O2 and Na1.0Mn0.7Fe0.05Al0.05Gd0.2O2 layers, was deposited on a substrate using magnetron sputtering to form a compositionally rich composite cathode material containing rare earth elements.

Benefits of technology

A sodium manganate composite cathode material with improved performance was prepared, exhibiting high first-cycle coulombic efficiency, excellent 1C specific capacity and good cycle retention. The electron transport performance was improved by the combination of rare earth elements and transition metals and nanocrystalline structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340366A_ABST
    Figure CN119340366A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium manganate composite positive electrode material. The material is prepared by the following method: depositing a Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Cu < 0.1 > Nd < 0.1 > O < 2 > layer on a substrate by magnetron sputtering; a Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Cu < 0.1 > Nd < 0.1 > O < 2 > layer is deposited on the Na < 1.0 > Mn < 0.7 > Fe < 0.05 > Cu < 0.05 > Nd < 0.2 > O < 2 > layer through magnetron sputtering; a Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Ti < 0.1 > Ce < 0.1 > O < 2 > layer is deposited on the Na < 1.0 > Mn < 0.7 > Fe < 0.05 > Cu < 0.05 > Nd < 0.2 > O < 2 > layer through magnetron sputtering; a Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Ti < 0.1 > Ce < 0.1 > O < 2 > layer is deposited on the Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Al < 0.1 > Gd < 0.1 > O < 2 > layer through magnetron sputtering; a Na < 1.0 > Mn < 0.7 > Fe < 0.1 > Al < 0.1 > Gd < 0.1 > O < 2 > layer is deposited on the Na < 1.0 > Mn < 0.7 > Fe < 0.05 > Al < 0.05 > Gd < 0.2 > O < 2 > layer through magnetron sputtering; and stripping the composite film from the substrate to obtain the sodium manganate composite positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium manganate composite positive electrode material and a preparation method thereof. Background Art

[0002] Due to the scarcity of lithium, there is a call in the industry to use sodium-ion batteries to replace lithium-ion batteries. Compared with lithium-ion batteries, sodium resources are abundant and widely distributed on the earth, and the mining cost is low, which makes sodium-ion batteries have great cost advantages in large-scale energy storage applications. With the increasing use of renewable energy, the demand for low-cost and efficient energy storage technology has become more urgent. Sodium-ion batteries have become a hot topic of research and are of great significance for solving the storage problem of renewable energy. Sodium manganate composite positive electrode material is a key component of sodium-ion batteries, and its research is of great significance to promoting the development of sodium-ion batteries.

[0003] Prior art CN117878307A (hereinafter referred to as Document 1) proposes a sodium manganate positive electrode material and its preparation method and application. The main design idea of ​​Document 1 is to use a variety of transition metal elements to replace the manganese element in traditional sodium manganate, so as to improve the performance of the positive electrode material of the sodium ion battery. The main defects of Document 1 are: 1. Since Document 1 adopts the traditional powder metallurgy method to prepare the positive electrode material of the battery, its positive electrode material composition is single, and the positive electrode material in a battery has only one component, which cannot give play to the advantages of composite materials; 2. Since Document 1 adopts the traditional powder metallurgy method to prepare the positive electrode material of the battery, Document 1 cannot form nanocrystals. After verification by the present invention, within a certain range, the larger the grain size, the worse the performance of the positive electrode material; 3. Document 1 does not consider the improvement of the performance of the positive electrode material by the special f-layer electrons of rare earth elements. Summary of the invention

[0004] To achieve the above object, the present invention provides a sodium manganate composite positive electrode material, which is prepared by the following method:

[0005] Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer;

[0006] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe0.05 Cu 0.05 Nd 0.2 O 2 layer;

[0007] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer;

[0008] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer;

[0009] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer;

[0010] The composite film is peeled off from the substrate to obtain a sodium manganate composite positive electrode material.

[0011] In a preferred embodiment, Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The thickness of the layer is 100-200nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2The thickness of the layer is 50-100nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 100-200nm, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 50-100nm, Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 100-200 nm.

[0012] In a preferred embodiment, Na is deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The specific layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

[0013] In a preferred embodiment, magnetron sputtering is used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The specific layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 200-300W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

[0014] In a preferred embodiment, magnetron sputtering is used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The specific layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 50-100V, and the sputtering temperature is 100-150°C.

[0015] In a preferred embodiment, magnetron sputtering is used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The specific layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 50-100V, and the sputtering temperature is 100-150°C.

[0016] In a preferred embodiment, magnetron sputtering is used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The specific layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 200-250W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

[0017] The present invention provides a method for preparing a sodium manganate composite positive electrode material, the preparation method comprising:

[0018] Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer;

[0019] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer;

[0020] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer;

[0021] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer;

[0022] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer;

[0023] The composite film is peeled off from the substrate to obtain a sodium manganate composite positive electrode material.

[0024] In a preferred embodiment, Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd0.1 O 2 The thickness of the layer is 100-200nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The thickness of the layer is 50-100nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 100-200nm, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 50-100nm, Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 100-200 nm.

[0025] Compared with the prior art, the present invention has the following advantages: the prior art adopts the traditional powder metallurgy method when preparing the positive electrode material, so the positive electrode material of the prior art has a single component, cannot play the advantages of the composite material, and cannot form nanocrystals; in addition, the prior art does not consider the special f-layer electrons of rare earth elements to improve the performance of positive electrode materials. In view of the defects of the prior art, through the method proposed by the present invention, the present invention can obtain a composite positive electrode material with rich components, and the composite positive electrode material of the present invention includes a large number of nanocrystals, and rare earth elements are added to the composite positive electrode material of the present invention. Through the combination of different types and contents of rare earth elements and transition elements, the composite positive electrode material of the present invention can improve battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic structural diagram of an embodiment of the present invention.

[0027] Figure 2 It is a method flow chart of an embodiment of the present invention.

[0028] Figure 3 This is a HRTEM photograph used to verify that nanocrystals can be formed according to one embodiment of the present invention.

[0029] Figure 4 This is a HRTEM photograph used to verify that nanocrystals can be formed according to one embodiment of the present invention. DETAILED DESCRIPTION

[0030] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0031] Figure 1 FIG. 1 is a schematic diagram of a structure of an embodiment of the present invention. As shown in the figure, the composite film layer prepared by the preparation method proposed by the present invention comprises: a substrate, a Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Layer and Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The composite film referred to in the present invention is a layer comprising Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O2 Layer and Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The substrate can be a silicon, aluminum oxide or glass substrate.

[0032] Figure 2 1 is a method flow chart of an embodiment of the present invention. As shown in the figure, the preparation method of the present invention comprises the following steps:

[0033] Step 1: Deposit Na on substrate using magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; it can be understood that the deposition of Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The target material of the layer is Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Target, Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The method for making the target material can refer to the prior art CN117832474A (hereinafter referred to as Document 2). For the purpose of full disclosure, the full text of the prior art Document 2 is incorporated herein. For the purpose of clarity, part of the content of Document 2 is quoted here to briefly introduce Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The preparation process of the target material. Sodium sulfate is selected as the sodium source, manganese carbonate is selected as the manganese source, iron nitrate is selected as the iron source, copper sulfate is selected as the copper source, and NdCl is selected as the Nd source. 2 (NdCl 2 The existence of can be proved by US Patent Document US7048809B2, and the substance can be purchased from chemical stores). According to the designed molar ratio of each element, weigh the corresponding amount of sodium sulfate, manganese carbonate, iron nitrate, copper sulfate, Nd source selection and NdCl 2Then the raw materials are mixed with citric acid to obtain a precursor, and then the precursor is placed in a mold, and the mold with the precursor is placed in a heat treatment furnace for sintering. The sintering atmosphere is an air atmosphere, the sintering temperature is 800 degrees Celsius, and the sintering time is 15 hours to obtain Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Target material.

[0034] Step 2: Magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Layer; Deposition Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Layer uses Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Target, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The preparation method of the target material is the same as the target material preparation method introduced in step 1, the only difference is the ratio of each raw material.

[0035] Step 3: Magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Layer; Deposition Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce0.1 O 2 Layer uses Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Target, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The preparation method of the target material is the same as that of the target material described in step 1. The only difference is the ratio of the raw materials. CeCl is used as the Ce source. 2 (CeCl 2 The existence of can be proved by US patent document US8052889B2).

[0036] Step 4: Magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Layer; Deposition Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Layer uses Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Target, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The preparation method of the target material is the same as that of the target material described in step 1. The only difference is the ratio of the raw materials. GdCl is used as the Gd source. 2 .

[0037] Step 5: Magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 Layer; Deposition Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 Layer uses Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 Target, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The preparation method of the target material is the same as that of the target material described in step 1. The only difference is the ratio of the raw materials. GdCl is used as the Gd source. 2 .

[0038] Step 6: Peeling the composite film from the substrate to obtain a sodium manganate composite positive electrode material. The composite film can be peeled from the substrate by mechanical peeling.

[0039] Example 1

[0040] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer; peeling the composite film from the substrate to obtain a sodium manganate composite positive electrode material.

[0041] Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The thickness of the layer is 100nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The thickness of the layer is 50nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 100nm, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 50nm, Na 1.0 Mn0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 100 nm.

[0042] Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30 sccm, the sputtering power is 100 W, the sputtering voltage is 100 V, and the sputtering temperature is 100°C.

[0043] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30 sccm, the sputtering power is 200 W, the sputtering voltage is 100 V, and the sputtering temperature is 100°C.

[0044] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30 sccm, the sputtering power is 100 W, the sputtering voltage is 50 V, and the sputtering temperature is 100°C.

[0045] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7Fe 0.1 Al 0.1 G 0.1 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30 sccm, the sputtering power is 100 W, the sputtering voltage is 50 V, and the sputtering temperature is 100°C.

[0046] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The specific layer is: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30sccm, the sputtering power is 200W, the sputtering voltage is 100V, and the sputtering temperature is 100°C. The composite positive electrode material obtained in Example 1 is used to assemble the battery. In order to ensure the comparability of the experimental results, the method of assembling the battery is referenced to Reference 1. For the purpose of clarity, the content of Reference 1 is partially quoted here to illustrate the method of assembling the battery. In the positive electrode sheet, the mass ratio of the composite positive electrode material, the conductive agent, and the binder of Example 1 is 96:1.5:2.5, the conductive agent is acetylene black, the binder is polyvinyl fluoride, and the solvent is N-methylpyrrolidone. The prepared positive electrode sheet, negative electrode sheet, electrolyte and diaphragm are assembled into a CR2032 button battery in a glove box filled with argon. The negative electrode is a metal sodium sheet, the electrolyte solvent is composed of dimethyl carbonate, diethyl carbonate, and ethyl carbonate, the volume ratio of the three is 1:1:1, and the solute of the electrolyte is 0.25M NaPF 6, the diaphragm model is Celgard 3000. Test items include first-cycle coulomb efficiency, 1C gram capacity, and 100-cycle cycle retention rate. The first-cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Example 1 is 99.5%, the 1C gram capacity is 142.5mAh / g, and the 100-cycle cycle retention rate is 97%. The electrical performance of the battery assembled based on the composite positive electrode material of Example 1 has a large increase compared with the prior art. The reasons for the increase can be attributed to: 1. Since the present invention prepares the composite positive electrode material by magnetron sputtering, the composite positive electrode material of the present invention is rich in components, and the layers of each component cooperate with each other, which improves the electron transport performance, thereby improving the battery performance; 2. Rare earth elements are added to the composite positive electrode material of the present invention. Rare earth elements have special f-layer electrons. The f-layer electrons interact with the d-layer electrons of the transition metal, which may form a special band structure, thereby helping to improve the electron transport performance; 3. A large number of nanocrystals are formed in the composite positive electrode material of the present invention, which also helps to improve the performance of the positive electrode material. In order to verify the formation of nanocrystals in the composite positive electrode material, the present invention provides Figure 3 and Figure 4 HRTEM photos of Figure 3 It is in Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 After the layer is formed, the sample with the substrate is directly mechanically cut (but the film layer is not peeled off), and then ion thinning is performed to obtain a sample that can be tested by TEM (the entire TEM experiment was commissioned to the Materials Science Laboratory of Zhengzhou University). It should be understood that unless a high temperature heat treatment is performed, the subsequent film sputtering will not make the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The lattice size of the layer increases, therefore, Figure 3 Although the samples in the experiment were not subjected to subsequent sputtering, Figure 3 It is completely possible to verify that 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The grains of the layer are nanocrystalline. Figure 3 As shown, in Figure 3Under the orientation of the electron beam and the sample, three grains can be clearly observed, and the size of these grains is less than 5nm. Figure 4 It's in Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 After the film is removed, the sample with the substrate is mechanically cut directly (but without peeling off the film layer), and then ion thinned to obtain a sample that can be tested by TEM. Figure 4 Under the orientation of the electron beam and the sample, a grain can be clearly observed. The direction of the larger grain has been indicated by the white line in the figure. It can be seen that the size of the grain is about 4nm.

[0047] Example 2

[0048] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer; peeling the composite film from the substrate to obtain a sodium manganate composite positive electrode material.

[0049] Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The thickness of the layer is 200nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The thickness of the layer is 100nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 200nm, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 100nm, Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 200 nm.

[0050] Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2The specific layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 150 W, the sputtering voltage is 150 V, and the sputtering temperature is 150°C.

[0051] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 300 W, the sputtering voltage is 150 V, and the sputtering temperature is 150°C.

[0052] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The specific characteristics of the layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 150 W, the sputtering voltage is 100 V, and the sputtering temperature is 150°C.

[0053] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The specific characteristics of the layers are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 150 W, the sputtering voltage is 100 V, and the sputtering temperature is 150°C.

[0054] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The specific layers are: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50sccm, the sputtering power is 250W, the sputtering voltage is 150V, and the sputtering temperature is 150°C. The method of assembling the battery is the same as in Example 1 and will not be repeated here. The first cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Example 2 is 99.3%, the 1C gram capacity is 145.4mAh / g, and the 100-cycle cycle retention rate is 96.8%.

[0055] Example 3

[0056] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer; peeling the composite film from the substrate to obtain a sodium manganate composite positive electrode material.

[0057] Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The thickness of the layer is 150nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The thickness of the layer is 70nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 150nm, Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 70nm, Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 150 nm.

[0058] Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The specific layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 120 W, the sputtering voltage is 120 V, and the sputtering temperature is 120°C.

[0059] Magnetron sputtering was used to deposit Na1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The specific conditions of the layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 250 W, the sputtering voltage is 120 V, and the sputtering temperature is 120°C.

[0060] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The specific layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 120 W, the sputtering voltage is 70 V, and the sputtering temperature is 120°C.

[0061] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The specific layers are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 120 W, the sputtering voltage is 70 V, and the sputtering temperature is 120°C.

[0062] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G0.2 O 2 The specific layers are: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50 sccm, the sputtering power is 220W, the sputtering voltage is 120V, and the sputtering temperature is 120°C. The method of assembling the battery is the same as in Example 1 and will not be repeated here. The first cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Example 3 is 99.4%, the 1C gram capacity is 144.3 mAh / g, and the 100-cycle cycle retention rate is 97.2%.

[0063] Comparative Example 1

[0064] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2layer; the composite film is peeled off from the substrate to obtain a sodium manganate composite positive electrode material. The remaining process parameters are the same as in Example 1 and will not be repeated here. The method for assembling the battery is the same as in Example 1 and will not be repeated here. The first-cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Comparative Example 1 is 93.4%, the 1C gram capacity is 129.3 mAh / g, and the 100-cycle cycle retention rate is 92.2%. Based on the comparison between Comparative Example 1 and Examples 1-3, it can be seen that omitting certain film layer structures will lead to a significant decrease in battery performance. The reason for this phenomenon may be that the various film layers cooperate with each other. If certain film layers are omitted, it may lead to increased stress between the remaining film layers and increased lattice distortion, which obviously adversely affects the electron transport characteristics. In addition, omitting a certain film layer may cause the coordination between the f electrons of various rare earth elements and the d electrons of transition metals to fail.

[0065] Comparative Example 2

[0066] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G0.2 O 2 layer; the composite film is peeled off from the substrate to obtain a sodium manganate composite positive electrode material. The remaining process parameters are the same as those in Example 1 and will not be repeated. The method for assembling the battery is the same as that in Example 1 and will not be repeated. The first cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Comparative Example 2 is 94.4%, the 1C gram capacity is 126.3mAh / g, and the 100-cycle cycle retention rate is 93.2%. The explanation for the performance degradation of Comparative Example 2 is the same as that of Comparative Example 1.

[0067] Comparative Example 3

[0068] The positive electrode material was prepared by the following method: Na was deposited on the substrate by magnetron sputtering. 1.0 Mn 0.7 Fe 0.1 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Ti 0.05 Ce 0.2 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.05 Ti 0.05 Ce 0.2 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 layer; using magnetron sputtering on Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 layer; the composite film is peeled off from the substrate to obtain a sodium manganate composite positive electrode material. The remaining process parameters are the same as those in Example 1 and will not be repeated here. The method of assembling the battery is the same as that in Example 1 and will not be repeated here. The first-cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Comparative Example 3 is 94.8%, the 1C gram capacity is 134.3mAh / g, and the 100-cycle cycle retention rate is 94.2%. The reason for the performance degradation of Comparative Example 3 is that the composition ratio is unreasonable, which may lead to the failure of the coordination between the f electrons of various rare earth elements and the d electrons of transition metals. It will also lead to increased stress between the film layers, lattice distortion, and adversely affect electron transport.

[0069] Comparative Example 4

[0070] The composite positive electrode material of Example 1 is first heat treated at 700 degrees Celsius for 10 hours, and the heat treatment atmosphere is argon. The composite positive electrode material after heat treatment is used to assemble the battery. The method of assembling the battery is the same as that of Example 1 and will not be repeated here. The first-cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Comparative Example 3 is 95.8%, the 1C gram capacity is 136.5mAh / g, and the 100-cycle cycle retention rate is 94.5%. The reason for the performance degradation of Comparative Example 4 is that the grain size becomes larger. It can be understood that after the nanocrystalline material is heat treated, the grain size will become larger. Comparative Example 4 heat treats the composite positive electrode material of Example 1, so that the grain size of the composite positive electrode material of Comparative Example 4 is larger than that of Example 1. Obviously, the larger grain size adversely affects the battery performance.

[0071] Comparative Example 5

[0072] Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 The thickness of the layer is 300nm, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The thickness of the layer is 300nm, Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O 2 The thickness of the layer is 300nm, Na1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O 2 The thickness of the layer is 300nm, Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O 2 The thickness of the layer is 300 nm. The other process parameters are the same as those in Example 1 and will not be described in detail. The film layer obtained in Comparative Example 5 has obvious cracks, which indicates that there will be a large number of defects at the interface between the film layers. Since the film prepared in Comparative Example 5 is a substandard product, no electrical performance test was performed.

[0073] Comparative Example 6

[0074] Magnetron sputtering was used to deposit Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O 2 Na is deposited on the layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The specific layer is: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 50sccm, the sputtering power is 500W, the sputtering voltage is 400V, and the sputtering temperature is 120°C. The remaining process parameters are the same as in Example 1 and will not be repeated here. The method of assembling the battery is the same as in Example 1 and will not be repeated here. The first cycle coulomb efficiency of the battery assembled based on the composite positive electrode material of Comparative Example 6 is 92.4%, the 1C gram capacity is 116.3mAh / g, and the 100-cycle cycle retention rate is 85.2%. The reason for the performance degradation of Comparative Example 6 is that due to the deterioration of process parameters, Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O 2 The layer itself may have a large number of microscopic defects, and the interface between the layer and its two adjacent layers may also have a large number of defects, and the stress between the interfaces is large and the lattice distortion is large, which may cause the battery performance to deteriorate rapidly.

[0075] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A sodium manganate composite positive electrode material, characterized in that: The material is prepared by the following method: Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O2 layer; The composite film is peeled off from the substrate to obtain the sodium manganate composite positive electrode material.

2. The material according to claim 1, wherein The Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 The thickness of the O2 layer is 100-200nm, and the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 The thickness of the O2 layer is 50-100nm, and the Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 The thickness of the O2 layer is 100-200nm, and the Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 The thickness of the O2 layer is 50-100nm, and the Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 The thickness of the O2 layer is 100-200nm.

3. The material according to claim 2, wherein Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 The specific conditions of the O2 layer are as follows: the magnetron sputtering power source is a radio frequency power source, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

4. The material according to claim 3, wherein Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 The specific conditions of the O2 layer are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 200-300W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

5. The material according to claim 4, wherein Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 The specific conditions of the O2 layer are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 50-100V, and the sputtering temperature is 100-150°C.

6. The material according to claim 5, wherein Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 The specific conditions of the O2 layer are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 100-150W, the sputtering voltage is 50-100V, and the sputtering temperature is 100-150°C.

7. The material according to claim 6, wherein Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 The specific conditions of the O2 layer are as follows: the magnetron sputtering power supply is a radio frequency power supply, the sputtering atmosphere is an argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 200-250W, the sputtering voltage is 100-150V, and the sputtering temperature is 100-150°C.

8. A method for preparing a sodium manganate composite positive electrode material, characterized in that: The preparation method comprises: Deposition of Na on substrate by magnetron sputtering 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 O2 layer; Using magnetron sputtering, the Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 Na is deposited on the O2 layer 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 O2 layer; The composite film is peeled off from the substrate to obtain the sodium manganate composite positive electrode material.

9. The preparation method according to claim 8, wherein The Na 1.0 Mn 0.7 Fe 0.1 Cu 0.1 Nd 0.1 The thickness of the O2 layer is 100-200nm, and the Na 1.0 Mn 0.7 Fe 0.05 Cu 0.05 Nd 0.2 The thickness of the O2 layer is 50-100nm, and the Na 1.0 Mn 0.7 Fe 0.1 Ti 0.1 Ce 0.1 The thickness of the O2 layer is 100-200nm, and the Na 1.0 Mn 0.7 Fe 0.1 Al 0.1 G 0.1 The thickness of the O2 layer is 50-100nm, and the Na 1.0 Mn 0.7 Fe 0.05 Al 0.05 G 0.2 The thickness of the O2 layer is 100-200nm.

Citation Information

Patent Citations

  • Lithium nickel manganese oxide positive electrode thin film material and preparation method thereof

    CN116005120A

  • Composite multilayer magnesium ion battery positive electrode material and preparation method thereof

    CN116732482A

  • Preparation method of layered oxide of sodium-ion battery

    CN117253968A

  • Pre-lithiated lithium ion positive electrode material, and preparation method therefor and use thereof

    US20230327071A1